Effect of viscoelasticity on displacement processes in porous media - Jung, Michael; Shakeri, Pegah; Seemann, Ralf (Frontiers in Physics, 2023)
Improving the displacement efficiency of capillary entrapments in porous media by adding high molecular weight polymers to the invading phase has various industrial applications, from enhanced oil recovery to soil remediation. Apart from an increased viscosity contrast compared to regular water flooding, the flow of viscoelastic polymer solutions exhibits unstable flow behavior even at small Reynolds numbers, which can lead to an additional displacement mechanism of the capillary entrapments. In this work, we employ a microfluidic approach to unravel the underlying physics and mechanism of this enhanced pore scale displacement. To this end, we show that the major complex topological flow features in a typical porous medium can be mimicked by a flow geometry consisting of a single capillary entrapment connected to two symmetric serpentine channels. This design excludes the effect of viscous stresses and allows direct focus on displacement processes driven solely by elastic stresses. We show that the unique viscoelastic fluid features, such as the significant storage and release of elastic stresses and first normal stress difference, combined with the flow geometry, lead to purely elastic instability and secondary flow, which in turn provide the stresses necessary to overcome the capillary threshold and displace the capillary entrapment.